STRATEGI PENGEMBANGAN PERDESAAN KAWASAN PERBATASAN, STUDI KASUS: KAWASAN PERBATASAN REPUBLIK INDONESIA-AMBENU REPUBLIK DEMOKRATIK TIMOR LESTE - Samsul Ma’rif (Diponegoro University, 2012)
Ambenu border area is an area which is included in East Nusa Tenggara Province and bound to Republic Democratic of Timor Leste directly. Ambenu is less develop area and has a lot of problems, include economic, socio-culture and nation safety aspect, whereas it has a lot of potencies to develop into an area which can compete with other countries. Therefore, it needs region development strategies as a need to border area development planning. Dealing with it, Ambenu border area has a role as the frontliner of Indonesian Republic teritory by counting on its potencies of farming sector. So that, Ambenu can develop related to its potencies and problems and can increase its prosperity community. This paper will discuss about development strategies of Ambenu border area by identifying the potencies and problems, tipology of border village based on its potencies and problems by using scoring method, public infrastructure’s service by using Schallogram Guttman and structuring development strategies by using grand strategies method.